Information needs in patients with bladder cancer undergoing radical cystectomy – A qualitative review with thematic synthesis. (December 2022) - Ståhlgren, Malin; Forsell, Camilla; Drott, Jenny
Abstract: Purpose: Worldwide, bladder cancer is the eleventh most common cancer. Self-care is significant after surgery and optimal information needs to be individualized. This will help the patient to understand and become involved in their own care. This study investigated experiences of information needs in patients with bladder cancer undergoing radical cystectomy. Methods: A qualitative review study with a thematic synthesis according to the PRISMA Statement Guidelines was performed. Results: Thirteen peer-reviewed original articles were included. This review highlighted that patient experienced unmet information needs about postoperative care and self-care. Patients also experienced receiving too much information in a limited time. This led to difficulties in understanding and processing the information. Patients also experienced limited information about sexual and psychological support and requested more information about physical activity. Conclusion: Information is essential but needs to be adapted and based on person-centred care principles related to the patients' needs and wishes. Unmet needs impact patients' lives and are associated with misunderstandings and insecurity, which need to be considered in cancer nursing. Clinical trial registration: The review was not registered. Highlights: Patients with cancer undergoing cystectomy experienced unmet information needs. Information needs to be individual tailored through the trajectory of illness. Patients with bladder cancer unmet needs must be considered in cancer nursing.